Dysregulated cancer cell transdifferentiation into erythrocytes is an additional metabolic stress in hepatocellular carcinoma - Abigail Hughes; Gurtej K Dhoot (Tumor Biology)
A number of human and canine hepatocellular carcinoma tissues showed clear signs of hypoxia indicated by HIF1α-activation and the presence of large clusters of cells resembling erythrocytes at different stages of nuclear elimination without any defined endothelial cell lining or blood vessel walls. Differentiated erythrocytic identity of such cells in hepatocellular carcinoma tissues was apparent from their non-nucleated and evolving basophilic to eosinophilic staining characteristics. In addition to the fully differentiated non-nucleated mesenchymal cell clusters, the onset of erythroblastic transdifferentiation was apparent from the activation of Glycophorin A, a marker of erythrocytic progenitors, in some epithelial cancer cells. Activation of canonical Wnt signalling in such tumours was apparent from the expression of Wnt2 ligand and active β-catenin translocation into the nucleus indicating Wnt signalling to be one of the key signalling pathways participating in such cell transdifferentiation. Sonic hedgehog and bone morphogenetic protein signalling along with Sulf1/Sulf2 activation was also observed in such hepatocellular carcinoma tissue samples. The presence of stem cell markers and the cell signalling pathways associated with erythropoiesis, and the detection of messenger RNAs for both α and β haemoglobins, support the assumption that hepatocellular carcinoma cells have the potential to undergo cell fate change despite this process being dysregulated as indicated by the lack of simultaneous generation of endothelial cell lining. Lack of blood vessel walls or endothelial cell lining around erythrocytic clusters was confirmed by non-detection of multiple blood vessel markers such as vWF, CD146 and smooth muscle α-actin that were clearly apparent in normal and unaffected adjacent regions of hepatocellular carcinoma livers. In addition to the activation of Glycophorin A, transdifferentiation of some hepatocellular carcinoma hepatocytes into other cell fates was further confirmed by the activation of some stem cell markers, for example, NANOG and OCT4 transcription factors, not only by reverse transcription polymerase chain reaction but also by their restricted expression in such cells at protein level.